Drought resistance of Argania spinosa L. colonized by the arbuscular mycorrhizal fungus Rhizophagus irregularis varies according to accession - Ganoudi, Matike; El Malahi, Soumia; Manan, Nouhaila; Ibriz, Mohammed; Calonne-Salmon, Maryline; Declerck, Stéphane (Frontiers in Plant Science, 2025)
Rhizophagus irregularis MUCL 41833 on three argan (Argania spinosa L. Skeels) accessions (Tidzi, Mejji, and City Hanchan) under well-watered (100% field capacity) and water-stressed (15% field capacity) conditions. Whatever the water regime, AMF colonization was observed in all accessions, but Tidzi showed significantly higher total root colonization than City Hanchan, while Mejji showed intermediate levels. Under well-watered conditions, the colonized plants exhibited higher biomass, root length, chlorophyll content, stomatal conductance, and root potassium (K) concentration in all accession. In the Mejji accession, colonized plants also had significantly higher shoot concentrations of phosphorus (P) and K. Under water-stressed conditions, plant response varied with accession. Compared to their respective controls, Mejii had significantly higher biomass, shoot K concentration, chlorophyll content, stomatal conductance, and reduced oxidative stress, Tidzi had also significantly higher biomass, root P and K concentration, and chlorophyll content with lower oxidative stress, while City Hanchan had significantly higher biomass and root P concentration but had higher H2O2 concentration. We can conclude that mycorrhization benefits all three accessions under stress conditions, with the Mejji and Tidzi accessions responding more favorably than the City Hanchan accession. These results highlight the role of AMF in improving argan tree performance under water-limiting conditions and demonstrate the variability in response between accessions.